Socioeconomic determinants of nutritional behaviors of households in Fars Province, Iran, 2018 - Foroozanfar, Zohre; Moghadami, Mohsen; Mohsenpour, Mohammad Ali; Houshiarrad, Anahita; Farmani, Azam; Akbarpoor, Mohsen Ali; Shenavar, Razieh (Frontiers in Nutrition, 2022)
Introduction: Households dietary habits are affected by their environment and socioeconomic status (SES). This study aims to investigate eating behaviors and determine the factors affecting nutritional status in households in Fars province on in 2018. Method: In the present cross-sectional study, urban and rural households were selected using multistage sampling method. A questionnaire was employed applied to interview the mother or householder to record the demographic, Socio-economic status (SES), and dietary habits of the family for major food items commonly used. Logistic regression model was used to analyze the data. The P-value less than 0.05 was considered significant. Results: In total, 6429 households participated in the study. The majority of households use traditional flat breads purchased bread, low-fat milk and liquid/cooking oil. Frying was the most prevalent method of cooking. Parents’ level of education and SES Socio-economic status was associated with type of consumed bread, milk and dairy, methods of food preparation, adding salt at the table, eating out and fast-food usage. Parents’ higher level of education was significantly associated with salt storage in optimal conditions and not using salt before tasting the meal. Conclusion: Most of the households had healthy practice, especially in consumption of certain oils and methods of preparing their food as well as keeping salt in an optimal condition and using iodized salt. The most important unhealthy nutritional behavior was high consumption of fast food and outdoor food, especially in urban regions. Unhealthy dietary habits were more prevalent in households with low household and regional SES. Both household and regions with higher SES had better dietary habits.